In Cryptanalysis and Improvement of the Zhu et al.'s Authentication Protocol - Mahdi Azizi; Abdolrasoul Mirghadri; Nasour Bagheri (Institute of Advanced Engineering and Science, 2013)
Zhu et al. recently have proposed an authentication prpotocol forRFID systems. In this paper, we analyze its security and explain itssecurity drawbacks. More precisely, we present traceability attackagainst this protocol. In addition, we propose an improvement on theZhu et al.'s to resists these security drawbacks. Finally, weinvestigate the formal security of the improved protocol based on theBAN logic method.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.2077